Association between muscle quality index and periodontal disease among American adults aged ≥ 30 years: a cross-sectional study and mediation analysis - Jukun Song; Yadong Wu; Hong Ma; Junmei Zhang (BMC, 2023)
Abstract Objective The muscle quality index (MQI) is a measurement of muscle quality that is directly related to overall health. There has been little study on the relationship between the muscle quality index and periodontitis in American people beyond 30 years. Therefore, this study aimed to explore the link between periodontitis and Muscle quality index (MQI) in older Americans. Methods Three thousand two hundred fifty-eight individuals (aged 30 to 59) who participated in the National Health and Nutrition Examination Survey (NHANES) 2011-2014 were considered eligible for the cross-sectional investigation. A hand dynamometer was used to determine the handgrip strength (HGS). Dual-energy X-ray absorptiometry was employed to calculate ASM (DXA). MQIArm was calculated by dividing the dominant hand's HGS by the dominant arm's ASM (in kg/kg). MQIApp was calculated by dividing the dominant hand's HGS by the ASM (in kg/kg). MQItotal was calculated by dividing the sum of the dominant and non-dominant hands by the ASM (in kg/kg). To investigate the link between muscle quality index and periodontal disease, the weighted multivariable logistic regression models were used. Using generalized additive models, it was determined if a nonlinear connection existed. Then, we developed a two-piece linear regression model and calculated the inflection point using a recursive approach. A mediation study was performed to determine how much of the impact of MQItotal on periodontitis was mediated by potential variables. Results Three thousand two hundred fifty-eight participants from the United States were enrolled. The OR (95% CI) for the relationship between MQItotal and periodontitis in the regression model with fully adjusted variables was 0.69 (0.53-0.91), for the connection between MQIArm and periodontitis was 0.90 (0.84-0.97), and for the association between MQIApp and periodontitis was 0.49 (0.30-0.80). MQItotal and periodontitis were shown to have a J-shaped relationship with a change point of 3.64. Before the change point, the OR (95% CI) was 0.69 (0.58, 0.82). In the analysis of drinking and married status, the interaction was statistically significant. Analysis of mediation showed that alcohol use was responsible for 0.4% (0.10 to 1.2) of the effect of MQItotal on periodontitis. Conclusion In American adults aged over 30, the Muscle Quality Index (MQI) exhibited an independent negative correlation with moderate to severe periodontitis, demonstrating a J-shaped relationship. Furthermore, alcohol consumption may act as a mediator in the association between MQI and periodontitis.